PENGARUH HARGA, PROMOSI PENJUALAN, DAN SHOPPING LIFESTYLE TERHADAP IMPULSE BUYING PADA PLATFORM TIKTOK SHOP - Ferrary, Delvin; Lina, Lina (LPPM Universitas Multi Data Palembang, 2024)
This research was conducted with the aim of knowing the effect of the variables Price, Sales Promotion, and Shopping Lifestyle on Impulse Buying on the Tiktok Shop Platform. The population in this study are users of the Tiktok application with a sample of Tiktok Shop consumers on the Tiktok application. The sample in this study was determined using a non-probability sampling technique with a purposive sampling approach, namely 120 respondents. The results of this study indicate that the variables Price and Shopping Lifestyle partially have a positive and significant effect on Impulse Buying on the Tiktok Shop platform. While the Sales Promotion variable partially has no effect and is not significant on Impulse Buying on the Tiktok Shop platform. Keyword : Price, Sales Promotion, Shopping Lifestyle, Impulse Buying